The Influence Of Work Ethic, Employee Competence, And Communication Quality On Employee Performance At The LPD Of Padang Sambian Village - Natalia Kadu; Ida Bagus Raka Suardana (Journal of Management, Economic, and Accounting, 2026)
The primary objective of this study is to examine how work ethic, employee competence, along with communication quality collectively impact employee performance within LPD Desa Pakraman Padang Sambian. In conducting this research, a quantitative methodology was applied through survey techniques that encompassed 35 employee members as participants. Given the limited scale of the population, the entire group of employees was utilized as the study sample, commonly referred to as census sampling technique. Information was systematically gathered via structured survey instruments, and subsequently processed through multiple linear regression analysis. This analytical approach was specifically designed to assess how predictor variables influence workforce outcomes, both when examined collectively (simultaneous effect) and when analyzed separately (partial effect). The findings obtained from this research reveal that when assessed collectively (simultaneous testing), work ethic, employee competence, along with communication quality demonstrate a significant influence on employee performance outcomes. This particular discovery suggests the capability of these three factors to jointly contribute toward describing the variations observed in employee performance among employees working at LPD Desa Pakraman Padang Sambian. However, when individual assessment (partial testing) was conducted, the results indicated that only employee competence together with communication quality exhibited significant influence on employee performance. Meanwhile, work ethic did not demonstrate any significant influence in this partial examination.